2009
DOI: 10.1080/02607470903220414
|View full text |Cite
|
Sign up to set email alerts
|

Research capacity building in teacher education: Scottish collaborative approaches

Abstract: This paper examines the context for education research, including teacher education research, in Scotland. Concerns about research capacity are shared with other parts of the UK, but the distinctive context for teacher development and engagement in practitioner research create fertile ground for developments in teacher education research. Schemes such as 'Research to support Schools of Ambition' provide evidence of a shared commitment to teacher research. The national project, 'Applied Education Research Schem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 21 publications
(15 reference statements)
1
30
0
Order By: Relevance
“…TCs can potentially contribute to strengthen research and practice links by a) providing a context for sustained collaboration where the perspectives and expertise of various stakeholders are brought to bear, b) enhancing the ecological validity of research through the investigation of problems that are relevant and meaningful to participants' practice, and c) (potentially) contributing to the generation of new knowledge and understandings about teaching and learning (Cassidy et al 2008;Christie et al 2007;Christie and Menter 2009;Cochran-Smith and Lytle 1999).…”
Section: Teacher Communities As An Overarching Conceptmentioning
confidence: 99%
See 3 more Smart Citations
“…TCs can potentially contribute to strengthen research and practice links by a) providing a context for sustained collaboration where the perspectives and expertise of various stakeholders are brought to bear, b) enhancing the ecological validity of research through the investigation of problems that are relevant and meaningful to participants' practice, and c) (potentially) contributing to the generation of new knowledge and understandings about teaching and learning (Cassidy et al 2008;Christie et al 2007;Christie and Menter 2009;Cochran-Smith and Lytle 1999).…”
Section: Teacher Communities As An Overarching Conceptmentioning
confidence: 99%
“…Here we take up a broad definition of educational research as a means to develop a fundamental understanding of educational phenomena as well as to improve policy and practice (cf. Christie and Menter 2009). This definition includes both basic and more applied forms of research (e.g.…”
Section: How Do Teacher Communities Contribute To Linking Research Anmentioning
confidence: 99%
See 2 more Smart Citations
“…The proliferation of teacher research, by and about teacher researchers, supports his claim yet also depicts how the field has grown more complicated 461 (Cochran-Smith & Lytle, 1999;Leeman & Wardekker, 2013). For example, teacher-led research has been found to provide opportunities for meaningful professional development (Vrijnsen-de Cortea, den Brok, Kamp, & Bergen, 2013), critical thinking (Hagevik, Aydeniz, & Rowell, 2012), discovery learning (Gray, 2013), collaborative collegial learning (Christie & Menter, 2009), university-school partnerships (Arhar et al, 2013;Thornley et al, 2004), and educational policy development (Rust & Meyers, 2006). Cochran-Smith and Lytle (1999) suggest that because teacher research "is such a generative concept, it can be shaped and reshaped to further virtually any educational agenda" (p. 17).…”
Section: Teachers As Researchers: Benefits Challenges and Time An mentioning
confidence: 85%